Digitalization towards business resilience: SME partnership program at Ketut Bagong Rental, Bali - I Made Dwi Ardiada; Putu Chris Susanto; Gek Wulan Novi Utami (Universitas Muhammadiyah Magelang, 2023)
Ketut Bagong Rental is a tourism-related SME operating vehicle rental in Badung, Bali. The SME has been in business since 2008, with 13 employees and around 300 units of motorcycles and cars for rent. However, partners experience marketing problems that are still conventional with a 90% market share concentrated in Eastern Europe. The purpose of this community service is to implement a solution in the form of creating and training in website management, information systems, branding and digital marketing campaigns. From the series of activities in this project, Ketut Bagong Rental has experienced noticeable impact in terms of market diversification (the proportion is now 60-40, with new markets developing for Western Europeans, Australians, and US nationals as renters). In addition, the company is now more confident in charging a premium for their rental, such that even without any significant increase in the number of vehicles, the revenue has increased 30% compared to the beginning of this project. Business digitalization efforts have also resulted in the increased resilience of Ketut Bagong Rental in facing the competitive climate of vehicle rental in Bali.